Maternal insulin-like growth factor 1 and 2 differentially affect the renin–angiotensin system during pregnancy in the guinea pig. Issue 3 (June 2015) - Standen, Prue; Sferruzzi-Perri, Amanda N.; Taylor, Robyn; Heinemann, Gary; Zhang, Jamie V.; Highet, Amanda R.; Pringle, Kirsty G.; Owens, Julie A.; Kumarasamy, Vasumathy; Lumbers, Eugenie R.; Roberts, Claire T.
Abstract: Objective: Insulin-like growth factors (IGFs) are known to interact with the renin–angiotensin system (RAS). We previously demonstrated that administration of IGF1 to guinea pigs in early to mid pregnancy promotes placental function and fetal growth in mid to late gestation. Early administration of IGF2 had sustained, but not acute, effects on these parameters and also on placental structural differentiation. Here, we aimed to determine whether the IGFs interact with the placental RAS in early to mid gestation to modulate placental development and increase fetal growth and survival, and if IGF2 binding the IGF2R is implicated in the sustained effects of IGF2 treatment. Design: At day 20 of pregnancy, guinea pigs were infused with 1 mg/kg/day of IGF1, IGF2, Leu27 IGF2 or vehicle for 18 days and sacrificed on either day 62 (late pregnancy) or during the infusion period on day 35 (early–mid pregnancy). Placental structure at day 35 was analyzed using morphometric technique and expression of RAS genes in the placenta and placental and plasma renin activity were measured at both time points. Results: Compared with vehicle at day 35 of gestation, IGF1 infusion reduced the total midsagittal cross-sectional area of the placenta (− 17%, p  = 0.02) and the labyrinth area (− 22%, p  = 0.014) but did not alter the labyrinth volume nor labyrinth:interlobium ratios. IGF2 treatment did not affect placental structure. IGF1 did not alter placental mRNA for any of the RAS genes quantified at day 35 ( AGTR1, ACE, AGT, TGFB1 ) but increased TGFB1 expression by more than 16-fold ( p  = 0.005) at day 62. IGF2 increased placental expression of AGTR1 (+ 88%, p  = 0.03) and decreased AGT (− 73%, p  = 0.01) compared with the vehicle-treated group at day 35, and both IGF2 and Leu27 IGF2 increased expression of TGFB1 at day 62 by 9-fold ( p  = 0.016) and 6-fold ( p  = 0.019) respectively. Both IGFs increased the ratio of active:total placental renin protein (+ 22% p  = 0.026 p  = 0.038) compared to vehicle compared to vehicle at day 35 but not 62. At day 62, IGF2-treated mothers showed a marked increase in total plasma renin (+ 495%) and active renin (+ 359%) compared to vehicle but decreased the ratio of active to total renin by 41% ( p  = 0.042). Leu27 IGF2-treated animals had higher levels of placental active renin (+ 73%, p  = 0.001) and total renin (+ 71%, p  = 0.001) compared with the vehicle control. Conclusions: The data obtained in the current study suggest the potential for alternate roles for the induction of the RAS after IGF treatment. IGF1 and 2 treatments increase the activation of prorenin to renin in the placenta, possibly due to increased protease activity. In addition, IGF2 treatment in early pregnancy may enhance the maternal adaptation to pregnancy through stimulation of renin in the kidney. The sustained effects on placental differentiation and function after IGF2 treatment suggest therapeutic potential for exogenous administration of IGFs in improving pregnancy outcomes. Highlights: Pregnant guinea pigs were infused with IGF1, IGF2, Leu27 IGF2 or vehicle for 18 days. Both IGFs increased the ratio of active:total placental renin protein mid pregnancy. IGFs did not affect circulating active or total renin in the mother mid pregnancy. IGF2 treatment increased total and active plasma renin near term. Leu27 IGF2 increased placental total and active placental renin near term.